CURRICULAR MANAGEMENT AND POLICIES FROM THE PERSPECTIVE OF THE DISCIPLINE OF PHYSICAL EDUCATION - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei)
This study, in the context of the curricular reforms implemented in the Republic of Moldova, used a mixed methodology, a structured digital questionnaire that combines items on the Likert scale with qualitative comment sections, to investigate the perceptions of 40 physical education teachers from all districts of the country regarding the effectiveness of curricular management and policies, the degree of alignment of curriculum documents with educational standards and the relevance of the Curriculum Framework Plan. education in relation to the current needs and realities of the educational system. The main conclusions show a moderate concordance between the curriculum and national policies. The curricular documents are evaluated positively, however, it is criticized for rigidity, lack of flexibility and insufficient integration of disciplines. Teachers come up with proposals for developing them at the level of redistribution of classes, integration of subjects and increasing the autonomy of schools in order to adapt the curriculum to local needs. Keywords: curricular documents, teachers, physical education.